In vitro study on the deterioration of polypropylene hernia repair meshes. Issue 6 (25th October 2017) - Gil, Dmitry; Rex, James; Reukov, Vladimir; Vertegel, Alexey
Abstract: Despite the relative safety of the procedure, hernia repairs are often associated with chronic post‐operative pain. Although this complication has been linked among others to mesh deterioration, details of the processes that lead this deterioration are still unknown. This work aims to bridge this gap by analyzing the chemical, physical and structural alterations in hernia repair meshes exposed to oxidative stress in vitro . Here, we developed a methodology to characterize effect of oxidation stress on structure and properties of polymeric hernia repair meshes. It was shown that structural changes in polypropylene meshes exposed to oxidative stress may involve formation of cross‐links between the polymer chains, chain scissions, and hydrogen bonds between the carboxyl groups, which are formed in the material during the oxidation. These effects result in mesh stiffening, ultimately leading to chronic post‐operative pain. Moreover, we demonstrated that Composix meshes are more vulnerable to the oxidative stress when compared with UltraPro meshes. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2225–2234, 2018.